Control of surgical infections: Relato XXVII Congreso Uruguayo de Cirugía - Laca, Emilio (Cirugía del Uruguay, 1976)
A report is presented on the problem of control of infections in surgical units, considering that the magnitude and gravity of the situation, haoe cannot be postponed that is known by all and corrected.